KOMUNIKASI KONSULTATIF PENYULUH AGAMA ISLAM DI DAERAH PERBATASAN KALIMANTAN BARAT - Bob Andrian (Jurnal Bimbingan Penyuluhan Islam, 2019)
Religious Intructor is one of the spearheads of the government, especially the Ministry of Religion, to provide guidance and counseling to the community. Islamic Religius Instructors are also a profession that has a significant role in communicating Islamic values ​​to the wider community, especially Muslim communities in border areas that have limited access to urban centers. The person is called an Instructor, both functional, honorary religious counselors and someone who carries out voluntary guidance and counseling (Volunteer) work. In addition, religious counselors are also mentioned by some experts that "Religious Instructors are Attackers, The Lamp in the midst of darkness, that gives enlightenment and teach wisdom to the surrounding community". Based on this statement, it can be described that the Religious Instructor is like a lamp that light in the midst of the great threat and challenge to national morality. According to the Joint Decree of the Indonesian Ministery of Religion and the Head of the State staffing Agency number 574 and 178 of 1999, it states that there are three functions of religious instructors, namely; Informative and educative functions, consultative functions, and advocative functions. Therefore, it is quite interesting to conduct a comprehensive study of how communication is carried out by Islamic Religious Instructors in providing enlightenment and providing Consulative guidance to the development community, including those that occur in border areas, particularly in Sajingan Besar District, Sambas Regency, West Borneo.